Boosting Students’ Mathematical Self-Confidence with Guided Discovery Learning and Geogebra Assistance - Julia, Rida; Kania, Nia (Plusminus: Jurnal Pendidikan Matematika, 2024)
Tujuan penelitian ini adalah untuk mengetahui efektivitas model Guided Discovery Learning berbantuan GeoGebra dalam meningkatkan kemampuan pemecahan masalah matematis siswa, dengan fokus khusus pada rasa percaya diri. Penelitian ini menggunakan metodologi Sistematic Literature Review (SLR) yang meliputi tahap perencanaan, peninjauan, dan dokumentasi, dengan pengelompokan, analisis, dan penarikan kesimpulan dari data. Hasil penelitian menunjukkan guru dapat memanfaatkan pendekatan Guided Discovery Learning dengan bantuan GeoGebra untuk meningkatkan kemampuan pemecahan masalah matematis siswa dengan tetap memperhatikan tingkat kepercayaan diri. Siswa yang menggunakan model Guided Discovery Learning berbantuan GeoGebra mempunyai kemampuan pemecahan masalah matematis yang lebih baik. This research aims to determine the effectiveness of the Guided Discovery Learning model assisted by GeoGebra in improving students' mathematical problem-solving abilities, with a special focus on self-confidence. This research uses the Systematic Literature Review (SLR) methodology which includes planning, reviewing, and documentation stages, grouping, analysis, and concluding the data. The research results show that teachers can utilize the Guided Discovery Learning approach with the help of GeoGebra to improve students' mathematical problem-solving abilities while still paying attention to their level of self-confidence. Students who use the Guided Discovery Learning model assisted by GeoGebra have better mathematical problem-solving abilities.